Government Antipoverty Programmes and Small and Medium Enterprises Performance in Nigeria - Edoko, Tonna, D.; Ngige, Chigbo D.; Okoli, Ikechukwu M. (European Scientific Journal, ESJ, 2017)
Over the years the Nigerian government has come up with a number of antipoverty programmes aimed at fighting poverty by financing her growth induced sector- SMEs, yet, the country is still witnessing rising levels of poverty, corruption, unemployment, low human capital development, inadequate commercial bank credit, high lending rate and low standard of education, thus, affecting the performance of small scale enterprises. In other to address the conundrum, this study examines the effect of government antipoverty programmes on small and medium enterprises’ performance in Nigeria using econometric regression model of the Ordinary Least Square (OLS). From the regression analysis, the result showed that government antipoverty programmes, corruption, unemployment, human capital development, capital, lending rate and education conformed to the a priori expectations of the study and were statistically significant in explaining the SMEs’ performance in Nigeria. The study recommends that: In order to enhance the success of government antipoverty programmes in Nigeria, the programme should be implemented through the local government on the platform of cooperative societies so that the target population will benefit from it. A blueprint for handling corrupt officials should be embedded in the policy framework of the programme before implementation. The programme should be targeted at unemployed youths with real identity rather than sinking back the funds into the pockets of corrupt officials. Every intending beneficiary should be subjected to training/skill acquisition programme and occasional workshop in the line of trade he/she wants to venture into. Adequate funding at a good lending rate should be provided for any beneficiary of the programme in order to enhance the performance of the business in Nigeria.